ANALYSIS OF MANIPULATORS USAGE FOR AUTOMATION OF WORK WITH LAYING COMPLEXES IN SEWING PRODUCTION - BILASHOV, KOSTIANTYN; KOVALIOV, YURII; RUBANKA, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents an analytical study of robotic manipulators application for automating operations of laying complexes used in the sewing and textile industries. The paper emphasizes relevance of implementing automation and intelligent robotic systems in context of modern production requirements for high productivity, precision, and reduced labor intensity. The study identifies limitations of traditional roll-loading equipment and substantiates the necessity of introducing manipulator-based systems that ensure precise, safe, and efficient handling of fabric rolls. The research applies a comprehensive methodological approach combining review of scientific sources, analysis of modern equipment from leading global manufacturers such as Lectra, Gerber, Kuris, and Dalmec, as well as the generalization of industrial experience from textile enterprises. The paper analyzes main types of manipulators — pneumatic, hydraulic, electric, and servo-driven — and their role in the automation of laying complexes. Special attention is given to the Italian manufacturer Dalmec S.p.A., whose pneumatic manipulators are characterized by high load capacity, precision, and adaptability to various production environments. Examples of manipulator configurations are provided, including vacuum grippers, centering devices, and expandable mandrels used for handling textile rolls of different diameters and materials. Their integration enables accurate positioning, reduced risk of fabric damage, and enhanced operator safety. The results demonstrate that usage of robotic manipulators significantly improves material handling efficiency, reduces physical labor, minimizes fabric waste, and optimizes production logistics. Moreover, manipulators can be integrated into computer-controlled manufacturing systems, contributing to digitalization and intelligent production in the textile sector. The article concludes that the implementation of pneumatic and hydraulic manipulators represents a promising direction for the modernization of laying complexes, providing higher production flexibility, economic efficiency, and product quality in the garment and textile industries.